Sensors, Medical Image and Signal Processing - Westphal, R.; Managing Editor for the IMIA Yearbook Section on Sensor, Signal and Imaging Informatics (Yearbook of Medical Informatics, 2007)
To summarize current excellent research in the field of sensor, signal and imaging informatics.Synopsis of the articles selected for the IMIA Yearbook 2007.The selection process for this yearbook section “Sensor, signal and imaging informatics” results in five excellent articles, representing research in four different nations. Papers from the fields of brain machine interfaces, sound surveillance in telemonitoring, soft tissue modeling, and body sensors have been selected.The selection for this yearbook section can only reflect a small portion of the worldwide copious work in the field of sensors, signal and image processing with applications in medical informatics. However, the selected papers demonstrate, how advances in this field may positively affect future patient care.
Keywords: Medical informatics; International Medical Informatics Association; yearbook; sensors; signal and imaging informatics